1994
DOI: 10.1093/jnci/86.3.183
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Cigarette Smoking and Risk of Colorectal Adenoma and Colorectal Cancer in U.S. Men

Abstract: Our results highlight the need to intensify efforts to prevent smoking, especially among the young, and suggest a reduced threshold for screening for colorectal cancer among long-term smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
144
4

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(160 citation statements)
references
References 0 publications
12
144
4
Order By: Relevance
“…Recent prospective studies have suggested a positive association between long-term and heavy smoking and colon cancer (Giovannucci et al, 1994;Hsing et al, 1998;Terry et al, 2001). In our present study, no significant association was observed in relation to the quantity of cigarettes smoked except for rectal cancer risk in men.…”
Section: Discussioncontrasting
confidence: 78%
“…Recent prospective studies have suggested a positive association between long-term and heavy smoking and colon cancer (Giovannucci et al, 1994;Hsing et al, 1998;Terry et al, 2001). In our present study, no significant association was observed in relation to the quantity of cigarettes smoked except for rectal cancer risk in men.…”
Section: Discussioncontrasting
confidence: 78%
“…Thus, we could not evaluate smoking as a potential confounder or as an effect modifier. Data have been mixed on whether smoking is an independent risk factor for colorectal cancer, 26,27 and if anything a higher risk is restricted to those who have smoked for several decades. Thus, it is unlikely that smoking is an important confounder of the association between acrylamide and colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…17 Our data on smoking duration corroborate with the observed long induction period of cigarettes in colorectal carcinogenesis as suggested by 2 previous American cohort studies. 18,19 Previous studies on smoking and large bowel cancer in Chinese yielded negative results. This might be due to the following reasons.…”
Section: Smoking Habitmentioning
confidence: 99%